MENGENAL BEBERAPA MODEL SILVOFISHERI DAN FUNGSINYA ( KASUS REHABILITASI MANGROVE DI KABUPATEN PEMALANG DAN BREBES) - Salam, Heru; Kaliman, Windrati (Fakultas Kehutanan Institut Pertanian STIPER Yogyakarta, 2011)
Mangrove is known as type of ecosystem has such of multifunction. what more has strategic function service, it is able to support and stabilice strong coastal and land ecosystem. Therefore, in every single handling,especially in the effort on rehabilitation,it should focus on the needs of all stake holders involving in the use of mangrove.The application of silvofishery model in rehabilitation purpose is assumed to fullfil the multifunction criteria,so it has been applied and developed by most of the community.But on the other side it is worried that the less of peoples optimally support the achievement of rehabilitation purpose.Under this condition, modification of silvofishery should be planned without obeying the need of people and other institutions to the use of mangrove. Keywords: silvofishery model ,rehabilitation